FARMERS’ INCOME OF CASSAVA AND MAIZE INTERCROPPING SYSTEM IN DRY LAND AGRICULTURE - Restie Novitaningrum; Ferry Wisnu Saputro (Proceeding of International Conference on Science, Health, And Technology, 2022)
Dry land agriculture, a less fertile land, only a few commodities that planted such as cassava, maize, sweet potatoes and any kind of nuts. Cassava and maize are secondary crops that usually cultivate in dry land. Cassava and maize are strategic food commodities after rice. This study aimed to analyze farmers’ income of cassava and maize intercropping system on dry land agriculture in Karanganyar Regency, Central Java, Indonesia. 60 farmers were taken as research respondents consist of 30 farmers who planted Jalak Towo cassava variety intercropping with maize and 30 farmers who planted other cassava varieties intercropping with maize. The data were analyzed with the concept of farmers’ income by subtracting revenues and explicit costs. The results showed that the intercropping of Jalak Towo cassava variety and maizeE yielded better farmers’ income.